PENGARUH GUGUS FUNGSI CINCIN PIRIDIN, BENZEN, DAN ATOM NITROGEN PADA CINCIN PIRIDIN TERHADAP PENURUNAN KADAR PLASMA PIRIDOKSIN TIKUS WISTAR - Hafrizal Riza; Jordi Buannata (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
In this study, researchers will conduct further studies to determine the map of functional groups that have an affinity for neuropathy-causing enzymes in the pyridine ring functional group after previous research on pyridine ring substituents. Through this study, it will be known whether there is an effect of the N atom on the pyridine ring, and the structure of the benzene ring. Therefore, the three structures, namely benzohydrazide, butyrohydrazide, formohydrazide, and isoniazid control, will be tested for their effect on the inhibition of the pyridoxal phosphokinase enzyme in experimental rats to see the effect of changing functional groups on decreasing affinity for the pyridoxal phosphokinase enzyme receptor which can be indicated by a decrease in active pyridoxine levels in the blood. mouse. The three compound structures were then examined for their interactions with the pyridoxal phosphokinase enzyme through their effect on increasing levels of pyridoxal 5 phosphate which is the active form of pyridoxine, using the Ultraviolet-Visible Spectroscopy method which showed an accumulation of enzyme analog substrates from the three compound structures with substrates from the body. The results of the ultraviolet-visible spectroscopy test showed that the active pyridoxine levels of rats in the isoniazid, benzohydrazid, and formohydrazid groups and the negative control group were 160,259, 120,548, 107,086 and 104,490, respectively. Based on the results, it was concluded that benzohydrazide and formohydrazide did not have a pharmacophore group against the pyridoxine phosphokinase enzyme.